1982
DOI: 10.1536/ihj.23.771
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of double outlet right ventricle induced by electrical shocks to the conotruncus of the embryonic chick implications of tissue dynamics.

Abstract: SUMMARYElectrical shock stimulation of the conotruncal area induced a spectrum of double outlet right ventricle (DORV) in embryonic chicks at developmental stages 24-27. The device used to apply electrical potentials to the heart was constructed using a 9 battery, a push-button switch, and a 100 ohm, ten-turn potentiometer with a calibrated dial. The potentiometer was connected as a voltage divider with the outlet connected to an electrode pair. This allowed for a short voltage pulse (variable 0 to 9) to be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…20 In the late1970s, he instructed his fellows to study the effect of radiation and electric shock on cardiac development. 21,22 In the early 1980s, he told his fellows to study the effect of various drugs, such as a retinoic acid, bisdiamine, and nimustin. 23,24 They found that maternal administration of a retinoic acid caused heterotaxy syndrome and transposed great arteries in the mouse.…”
Section: Kawasaki Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…20 In the late1970s, he instructed his fellows to study the effect of radiation and electric shock on cardiac development. 21,22 In the early 1980s, he told his fellows to study the effect of various drugs, such as a retinoic acid, bisdiamine, and nimustin. 23,24 They found that maternal administration of a retinoic acid caused heterotaxy syndrome and transposed great arteries in the mouse.…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…In the early 1970s, together with Shizen Ishikawa, he noted that the frequencies of ventricular septal defect and anomalies of the aortic arch were high in chick embryos after centrifugation 20 . In the late1970s, he instructed his fellows to study the effect of radiation and electric shock on cardiac development 21 , 22 . In the early 1980s, he told his fellows to study the effect of various drugs, such as a retinoic acid, bisdiamine, and nimustin 23 , 24 .…”
Section: Basic Science In the 1970s And 1980smentioning
confidence: 99%